Comparative Study of Regeneration Potential in Three Rapeseed (Brassica napus L.) Genotypes (Plant Tissue Culture and Biotechnology, 2026)
Rapeseed (Brassica napus L.) is a major oilseed crop valued for its high content of omega-3 and omega-6 fatty acids; however, its yield potential is frequently limited by various biotic and abiotic stresses. The establishment of an efficient and reproducible in vitro regeneration system is therefore essential for genetic improvement of this crop. Explants (hypocotyl, epicotyl, and cotyledonary node) from eight-day-old seedlings were cultured on full-strength MS medium using different concentrations and combinations of plant growth regulators. The study successfully optimized an in vitro regeneration protocol for rapeseed cultivars BINA Sarisha-12, RT-35, and RT-38, identifying specific hormonal and explant requirements for each stage. Hypocotyls emerged as the most effective source for callus induction, peaking at 93.19% in BINA Sarisha-12, followed by 91.95% in RT-35, and 90.74% in RT-38., while cotyledonary nodes proved superior for shoot regeneration with a high frequency of 97.78%. Optimal shoot elongation was achieved using 2.5-3.0 mg/l BAP, whereas rooting efficiency was maximized using IBA for BINA Sarisha-12 and a synergistic IBA/IAA combination for the RT genotypes. Cotyledonary nodes were determined as the best explants for shoot regeneration and hypocotyls for callus induction, establish a highly efficient, genotype-specific framework essential for future CRISPR-Cas9 genome editing and genetic advancement in rapeseed.Plant Tissue Cult. & Biotech. 36(1): 49-56, 2026 (June)